2018
DOI: 10.1177/2045125318804364
|View full text |Cite
|
Sign up to set email alerts
|

Medication nonadherence in bipolar disorder: a narrative review

Abstract: A number of effective maintenance medication options exist for bipolar disorder (BD) and these are regarded as the foundation of long-term treatment in BD. However, nonadherence to medication is common in BD. For example, a large data base study in the United States of America (USA) showed that approximately half of patients with BD were nonadherent with lithium and maintenance medications over a 12 month period. Such nonadherence carries a high risk of relapse due to the recurrent nature of the illness and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(86 citation statements)
references
References 105 publications
(138 reference statements)
3
82
0
1
Order By: Relevance
“…In its clinical trial programme, overall adherence to G/P regimens has been reported at >95% with comparable rates among patients with psychiatric disorders, people who inject drugs and patients on stable opioid substitution therapy . Although treatment adherence was almost 90% in patients with bipolar disorder, nonadherence to medication was more common among patients with bipolar disorder in line with previous studies . However, it is conceivable that real‐world cohorts with more severe, untreated psychiatric disorders may be at‐risk for lower treatment adherence with DAAs including G/P.…”
Section: Discussionsupporting
confidence: 63%
“…In its clinical trial programme, overall adherence to G/P regimens has been reported at >95% with comparable rates among patients with psychiatric disorders, people who inject drugs and patients on stable opioid substitution therapy . Although treatment adherence was almost 90% in patients with bipolar disorder, nonadherence to medication was more common among patients with bipolar disorder in line with previous studies . However, it is conceivable that real‐world cohorts with more severe, untreated psychiatric disorders may be at‐risk for lower treatment adherence with DAAs including G/P.…”
Section: Discussionsupporting
confidence: 63%
“…Of note, female gender has been associated with suicide attempts in RC patients [52], supporting the hypothesis of a crucial role of sex hormones on the clinical course of BD [53]. Similarly, a higher presence of poor insight in RC versus NRC subjects has been reported by other authors [54], this aspect being consistent with the supposed long duration of illness and more advanced staging of this subtype of patients [55]. Finally, subjects with RC resulted to receive less frequently a current treatment with mood stabilizers and antidepressants.…”
Section: Variablessupporting
confidence: 72%
“…In 77% of patients, at least one reason for stopping treatment came from the patients’ providers whereas in only 18% had the patient decided to stop treatment. The risk of stopping treatment might reflect worsening pain, conflicts with or disengagement from providers, particularly during exacerbations of mental health disorders (eg, aberrant behaviors, substance misuse, or mania), symptoms related to withdrawal, or a combination of these factors 153839. Our findings suggest that future studies should include all patients prescribed opioids, not just those on long term treatment, and look at suicide behaviors in addition to outcomes of overdose.…”
Section: Discussionmentioning
confidence: 92%